Physical and Psychological Childbirth Experiences and Early Infant Temperament - Power, Carmen; Williams, Claire; Brown, Amy (Frontiers in Psychology, 2022)
Objective: To examine how physical and psychological childbirth experiences affect maternal perceptions and experiences of early infant behavioural style (temperament). Background: Unnecessary interventions may disturb the normal progression of physiological childbirth and instinctive neonatal behaviours that facilitate mother-infant bonding and breastfeeding. While little is known about how a medicalised birth may influence developing infant temperament, high impact interventions which affect neonatal crying and cortisol levels could have longer term consequences for infant behaviour and functioning. Methods: A retrospective internet survey was designed to fully explore maternal experiences of childbirth and her postnatal perceptions of infant behaviour. Data collected from 999 mother-infant dyads were analysed using Pearson’s correlations and multiple analyses of covariance, employing the Bonferroni method of correction to establish initially significant variables. Multiple linear regressions were conducted to determine major perinatal contributors to perceived early infant temperament. Results: Multiple regression analyses on each of the eight Mother and Baby Scales outcome variables indicated that early infant behavioural style (0-6 months) was largely predicted by subjective maternal states during and post childbirth, postnatal depression scores, maternal personality traits and infant age. For example, infant age (Beta = .440, p = .000) was the most significant predictor of Alert-Responsive infant behaviour, followed by maternal Postnatal Positive experience (Beta = .181, p = .000). In contrast, depression (EPDS) scores (Beta = .370, p = .000) were the most significant predictor of Unsettled-Irregular infant behaviour, followed by Anxious-Afraid Birth Emotions (Beta = .171, p = .000) and infant age (Beta = -.196, p = .000). Mothers also perceived their infants as more Alert-Responsive (Beta = .080, p = .010) and Easier overall (Beta = .085, p = .008) after a Supported birth experience. Conclusion: Maternal and infant outcomes were influenced by multiple physical and psychological perinatal variables. The mother’s subjective experience appeared to be of equal significance to more objective factors (e.g., birthplace/mode). Social support enhanced the mother’s childbirth experience, benefitting her perceptions of her baby’s early temperament. These findings provide further support for current World Health Organisation intrapartum guidelines (2018) on the importance of making childbirth a ‘positive experience’ for women.